Corporate governance and Shariah non-compliant risk in Islamic banks: evidence from Southeast Asia. Issue 2 (22nd November 2019) - Basiruddin, Rohaida; Ahmed, Habib
Abstract : Purpose: This study aims to investigate the relationship between corporate governance and Shariah non-compliant risk (SNCR) that is unique for Islamic banks. The study examines the roles of Shariah committee along with the board of directors in mitigating SNCR. Design/methodology/approach: The paper empirically investigates the implications of characteristics of board of directors and Shariah committee on the SNCR by using a sample of 29 full-fledge Islamic banks from Malaysia and Indonesia over the period 2007-2017. All data is hand collected from the Islamic banks' annual reports with the exception of country-level data collected from the World Bank database. Findings: The results show that banks with a smaller board size and higher proportion of independent board members are likely to have lower SNCR. The findings also indicate that the financial expertise and higher frequency of Shariah committee meetings reduces the SNCR. Collectively, the analysis shows that banks with strong corporate governance environments reduce SNCR. Practical implications: The findings of the study shed light on the relationship between corporate governance practice, Shariah committee characteristics and SNCR. The results can be used by different stakeholders such as policymakers, boards of directors and senior management of Islamic banks to mitigate SNCR. Originality/value: This study extends the literature on corporate governance and risk-taking by including additional dimensions of governance and risk type. The corporate governance mechanism at the board level is complemented by including the Shariah committee characteristics and SNCR which is relevant to Islamic financial institutions is examined.